2015
DOI: 10.1073/pnas.1506684112
|View full text |Cite
|
Sign up to set email alerts
|

Flow perfusion effects on three-dimensional culture and drug sensitivity of Ewing sarcoma

Abstract: Three-dimensional tumor models accurately describe different aspects of the tumor microenvironment and are readily available for mechanistic studies of tumor biology and for drug screening. Nevertheless, these systems often overlook biomechanical stimulation, another fundamental driver of tumor progression. To address this issue, we cultured Ewing sarcoma (ES) cells on electrospun poly(e-caprolactone) 3D scaffolds within a flow perfusion bioreactor. Flow-derived shear stress provided a physiologically relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 33 publications
5
104
2
Order By: Relevance
“…[99] The radially-aligned fibers can be prepared by utilizing a collector composed of a central point electrode and a peripheral ring electrode. [100] Randomly oriented nanofibers are capable of mimicking the ECM architecture of tumor tissue, and have been widely applied for the design of 3D cancer models [101] and biosensors for cancer cell detection, [102] capture and isolation [103] . In contrast with random nanofibers, the aligned feature greatly endows enhanced capabilities in regulating cancer cell behavior including cancer cell proliferation, migration and invasion [104] , gene expression [105] , and signal transduction [106] .…”
Section: Recent Progress In Electrospun Nanofibersmentioning
confidence: 99%
“…[99] The radially-aligned fibers can be prepared by utilizing a collector composed of a central point electrode and a peripheral ring electrode. [100] Randomly oriented nanofibers are capable of mimicking the ECM architecture of tumor tissue, and have been widely applied for the design of 3D cancer models [101] and biosensors for cancer cell detection, [102] capture and isolation [103] . In contrast with random nanofibers, the aligned feature greatly endows enhanced capabilities in regulating cancer cell behavior including cancer cell proliferation, migration and invasion [104] , gene expression [105] , and signal transduction [106] .…”
Section: Recent Progress In Electrospun Nanofibersmentioning
confidence: 99%
“…In a recent study, Santoro et al cultured Ewing sarcoma cells on an electrospun polymeric scaffold within a flow perfusion bioreactor and showed that flow-derived shear stress significantly enhanced the production of insulin-like growth factor-1 (IGF-1) over static conditions [143]; the IGF1/IGF-1 receptor pathway is a current clinical target for this pediatric disease. It was further demonstrated that drug response to an IGF-1 receptor inhibitor, dalotuzumab, was dependent on flow rate, underscoring the importance of mechanical stimulation on the cancer cell phenotype and drug sensitivity.…”
Section: Modeling the Complex Tumor Microenvironment In 3dmentioning
confidence: 99%
“…IGF-1R is a member of a larger superfamily of receptor kinases, and could sense and respond to mechanical stimuli in several nonchondrocytic cell types [6,25,26]. This study investigated and considered IGF-1R signals to be candidate signals for inducing chondrocyte proliferation by periodic mechanical stress.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%